(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Billions of people interact with social media daily. However, various users realize how every snap and press produced interactions eventually led to a large social network structure. Enthusiastic social media users, including mailings, pages, microblogs, and wikis, are willing to send personal or public messages, express strong views, raise awareness of the community in building partnerships, foster cultural heritage, and advancing growth. Social media professionals build, create and share digital content to tug together or develop resources to integrate their experiences, express their creative ideas. and offer support for friends and partners. The results are wide, dynamic networks connecting people with other residents, books, sites, ideas, and different articles. New tools are now capturing, analyzing, sharing, and creating knowledge through texts, folders, forums, blogging, uploading photos and videos, reviews, and concepts through the utilization of trillion experiences. The unseen connections between each folks are now more accentuate and available by machines as social media also appear as a standard forum for user interaction. Consequently, social network analysis will identify local and global trends, identify prominent actors, and analyze network dynamics, creating new potential for an exhaustive and groundbreaking visualization of a social network.